Social modeling of food choices in real life conditions concerns specific food categories. (1st July 2021) - Garcia, Armelle; Hammami, Alya; Mazellier, Lucie; Lagneau, Julien; Darcel, Nicolas; Higgs, Suzanne; Davidenko, Olga
Abstract: The social context of eating has a profound effect on consumption choices. Social modeling, that involves using others' behavior as a guide for appropriate consumption, has been well documented for food intake, but less is known about social modeling of food choices. Moreover, social modeling has mainly been studied in laboratory settings. We conducted an observational study in a self-service canteen to examine whether the food choices of an individual were influenced by the choice of the person ahead in the queue. We recorded food choices of 546 individuals (333 men and 211 women) and those of the person in front of them in the queue along a linear buffet. Starters were sub-categorized into salads, mixed starters (e.g. avocado shrimp mayonnaise), and cold meat starters, and desserts were sub-categorized into fruits, dairy products and pastries. There was a significantly higher probability of taking a starter in general (OR = 1.65, IC = 1.06–2.57, p = 0.03), a salad (OR = 1.78, CI = 1.08–2.93, p = 0.02), a mixed starter (OR = 2.98, CI = 1.42–6.05, p < 0.01), but not a cold meat, if the person ahead in the queue also took one compared to when the person ahead did not take one. No significant modelling was found for desserts which may be because almost all participants took a dessert. These results highlight that social modeling influences food choices, and that this phenomenon can be observed in a real life setting. These data also suggest that some food categories, such as starters, could be more susceptible to social modeling than are others. Finally, we observed modeling both between familiar and unfamiliar participants, which suggests that social norms could be used to promote healthier eating in a range of settings including friendship groups.